PENGARUH MEDIA GAMBAR FOTOGRAFI MATERI KEBERAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU TERHADAP HASIL BELAJAR SISWA DI KELAS IV SDN 16 TANJUNG BATU - Nia Natasyah; M. Juliansyah Putra; Sunedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to determine the effect of the use of photographic media material on ethnic and religious diversity in my country on the learning outcomes of fourth grade students at SDN 16 Tanjung Batu, because the completeness of class IV student learning outcomes at SD Negeri 16 Tanjung Batu, Tanjung Batu District, is classified as low with a value of 60. The type of research used is Experiment. The techniques used to collect data are observation, test and documentation techniques. The results of this study indicate that the use of photographic image media on the diversity of ethnicity and religion in my country has an effect on student learning outcomes in class IV SDN 16 Tanjung Batu. the tcount value is 7.090 while the ttable is df 48 with a level of 0.05, so ttable = 1.677. So it is stated that tcount > ttable = 7.090 > 1.677 so that tcount is declared significant where Ha is accepted and Ho is rejected. Thus, the hypothesis states that there is an influence of Photographic Image Media Material on the Diversity of Ethnic and Religious Ethnicities in My Country on Student Learning Outcomes in Class IV SDN 16 Tanjung Batu.